Penguatan Spiritualitas Kepemimpinan Kristen dalam Mengemban Amanat Agung Kristus di Era Digital - Binsen Samuel Sidjabat (Phronesis: Jurnal Teologi dan Misi, 2025)
This paper discusses the strategy for developing the spirituality of Christian leaders in fulfilling the call of the Lord Jesus to carry out His Great Commission. In this digital age, there are opportunities for Christian leaders to carry out the Great Commission creatively and to enrich their spirituality. However, this digital era also presents various temptations and challenges that can hinder the increase in spirituality that is indispensable in the preaching of the Gospel. With a qualitative approach and literature research methods, this paper argues that Christian leaders should be wise in responding to the opportunities presented by digital technology, thereby carrying out the Great Commission of the Lord Jesus Christ in faithfulness. Spirituality, resulting from a close relationship with the Lord Jesus, is essential in fulfilling His duties and callings. It is hoped that the thoughts in this paper will be useful for Christian leaders in the context of the church, theological education, and the public sphere.